2020
DOI: 10.3390/nu12082294
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Breakfast and Healthy Diet in School-aged Adolescents and Their Association with BMI, Weight Loss Diets and the Practice of Physical Activity

Abstract: Dietary habits are an important factor in the protection of adolescent health. The quality and frequency of breakfast and the various food groups can affect the wellbeing of this population group in both the short and long term. Research indicates that there is a range of relevant variables in the study of diet at this stage: following a weight loss diet, body mass index and the practice of physical exercise, amongst others. In this paper, all three variables are analysed, together with others of a demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…And finally, the design, protocol and methodology of the ENALIA study were made in accordance with the recommendations of the European Food Safety Agency (EFSA) "EU Menu" guidance recommendations [43,44]. The sample studied presents anthropometric data similar to those of other Spanish children of the same age [1, 6,21,22,31,32,36,37]. As far as misreporting is concerned, our results coincide with those of Coulthard et al [2] which indicated that under-reporting may have been more prevalent for the children in the 11-18 years age group, who provided their own food consumption, in contrast to children in the younger age group, whose diaries were completed by their parents or caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And finally, the design, protocol and methodology of the ENALIA study were made in accordance with the recommendations of the European Food Safety Agency (EFSA) "EU Menu" guidance recommendations [43,44]. The sample studied presents anthropometric data similar to those of other Spanish children of the same age [1, 6,21,22,31,32,36,37]. As far as misreporting is concerned, our results coincide with those of Coulthard et al [2] which indicated that under-reporting may have been more prevalent for the children in the 11-18 years age group, who provided their own food consumption, in contrast to children in the younger age group, whose diaries were completed by their parents or caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ANIBES (“anthropometric data, macronutrients and micronutrients intake, practice of physical activity, socioeconomic data and lifestyles in Spain”) study defined breakfast as the first intake declared by the participant after overnight sleeping, and found that 93.4% of children aged 9–12 years and 80.1% of children aged 13–17 years reported breakfast on a regular basis, while 6.6% and 19.9% of children aged 9–12 and 13–17, respectively, reported having breakfast irregularly or not having breakfast [ 23 , 37 ]. Guevara et al [ 21 ] evaluated the quality of the breakfast of a group of Spanish adolescents (11–18 years old) based on the weekly frequency with which a “full breakfast” was consumed (when in addition to a glass of milk or a piece of fruit, the respondent eats something else), and observed that 24.5% of adolescents had a poor breakfast (skipping it two or more days a week), and it was more frequent as adolescents are older. Finally, in the ALADINO (“Alimentación, Actividad Física, Desarrollo Infantil y Obesidad”) study (carried out in a representative sample of the Spanish school population aged 6 to 9 years) 68,3% of families indicated that their children ate more than a drink (milk, juice, infusions, …) for breakfast every day and only 2.2% indicate that children never eat breakfast [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight selected study articles were published between 2015 and 2020. There were four articles whose research was conducted in Asia [17][18][19][20]; two articles on Europe [11,13]; one article on North America [18]; and one other article from Africa [19]; which have been shown in Table 1.…”
Section: Descriptive Characteristics Of Study Articlesmentioning
confidence: 99%
“…The articles synthesized in this literature review have an intervention setting in schools with a study sample of 13-15 years of age [11,19,20,22]; 13-14 years [13,18], 14 years [15]; and 14-15 years [18]. The sample size for these articles ranged from 79 to 4220 children [11,13,[17][18][19][20][21][22]. These data are presented in a journal collection in Table 2.…”
Section: Descriptive Characteristics Of Study Articlesmentioning
confidence: 99%